Synthetic Glycoforms Reveal Carbohydrate‐Dependent Bioactivity of Human Saposin D. Issue 19 (5th April 2017) - Graf, Christopher G. F.; Schulz, Christian; Schmälzlein, Marina; Heinlein, Christian; Mönnich, Manuel; Perkams, Lukas; Püttner, Markus; Boos, Irene; Hessefort, Markus; Lombana Sanchez, Jose Nelson; Weyand, Michael; Steegborn, Clemens; et al.
Abstract: The main glycoforms of the hydrophobic lysosomal glycoprotein saposin D (SapD) were synthesized by native chemical ligation. An approach for the challenging solid‐phase synthesis of the fragments was developed. Three SapD glycoforms were obtained following a general and robust refolding and purification protocol. A crystal structure of one glycoform confirmed its native structure and disulfide pattern. Functional assays revealed that the lipid‐binding properties of three SapD glycoforms are highly affected by the single sugar moiety of SapD showing a dependency of the size and the type of N‐glycan. Abstract : Lipid wrap : The main glycoforms of the hydrophobic lysosomal glycoprotein saposin D (SapD) were synthesized by native chemical ligation. In functional assays the lipid‐binding properties of three SapD glycoformsS1 –S3 were found to be affected by the sugar moiety of SapD and showed a dependency on the size and the type of N ‐glycan.